2019
DOI: 10.1002/jper.19-0064
|View full text |Cite
|
Sign up to set email alerts
|

AT1 receptor antagonism promotes bone loss attenuation in experimental periodontitis, blocks inflammatory mediators, and upregulates antioxidant enzymes and bone formation markers

Abstract: Background:The initiation and progression of periodontitis might involve a local renin-angiotensin system in periodontal tissue. This study hypothesized that Losartan treatment could promote protection to rats submitted to experimental periodontitis (EP) by attenuating alveolar bone loss due to reduction in inflammatory cytokines, better reactive oxidant species regulation and maintenance of the balance between bone formation and resorption factors. Methods:One hundred and thirty rats were submitted to EP with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…With regard to the characteristics of the population, one study examined a sample made only of postmenopausal women 20 , one was on elderly people (≥ 65 years old) 21 , four studies on former or current smokers 22 25 , and one study included only smokeless tobacco users 26 . For systemically compromised patients five studies included only subjects with treated type 2 diabetes 27 30 , and the other studies were on systemically healthy subjects. The maximum reported follow-up was 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the characteristics of the population, one study examined a sample made only of postmenopausal women 20 , one was on elderly people (≥ 65 years old) 21 , four studies on former or current smokers 22 25 , and one study included only smokeless tobacco users 26 . For systemically compromised patients five studies included only subjects with treated type 2 diabetes 27 30 , and the other studies were on systemically healthy subjects. The maximum reported follow-up was 12 months.…”
Section: Resultsmentioning
confidence: 99%
“…The present study results demonstrated that the AT1R blocker, TELM, had a protective effect on PD-induced inflammation and alveolar bone loss in hypertensive animals by decreasing the production of cytokines and reducing the expression of osteoclast markers in hypertensive animals. The action of the local RAS in periodontal tissues has already been described and is associated with periodontal inflammatory damage (Santos et al, 2009;Santos et al, 2015;Dionisio et al, 2019;Oliveira et al, 2019). The SHR strain is known to present alterations in the systemic RAS (Schiffrin et al, 1984;Ohta et al, 1996;Gouldsborough et al, 2003) as well as intrinsic bone impairment associated with the hypertensive genotype and phenotype (Manrique et al, 2012;Landim de Barros et al, 2016;Tiyasatkulkovit et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that SHRs suffer from more severe periodontal inflammation (Bonato et al, 2012), and the inhibition of the RAS can attenuate the resorption of alveolar bone (Dionisio et al, 2019;Oliveira et al, 2019). In this study, we aimed to evaluate the local bone metabolism of normotensive and hypertensive animals with PD following treatment with TELM, as the effects of TELM on bone metabolism are yet to be clearly understood.…”
Section: Introductionmentioning
confidence: 99%
“…AT2 receptors are mainly expressed during fetal development [ 22 ], which decline rapidly after gestation; persist in diminished numbers in the kidneys, vascular endothelium, and a few other tissues during adulthood; and may be re-expressed and upregulated in response to injury, heart failure, or sodium depletion [ 23 ]. Studies have shown the relationship between antagonist drug of the AT1 receptor and periodontal disease [ 11 , 12 , 13 ]. On the other hand, Enalapril and losartan use in female rats suggests that regular use of these two drugs is not associated with changes in bone density [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of AT1 receptor antagonism to bone tissue metabolism in the presence of the periodontal disease has been shown in the literature [ 11 , 12 ]. This is an original paper that describes the role of silencing AT1 or AT2 receptors in a periodontal inflammation experimental model induced by Porphyromonas gingivalis -Lipopolysaccharides (LPS).…”
Section: Introductionmentioning
confidence: 99%